Examining Structural and Social Drivers of Hepatitis B Vaccination Across Diverse Clinical Settings - Alisa Vidwans; Anita Narkhede; Emily Coughlin; Lisa J Sanders (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Hepatitis B is a major cause of liver cancer in the United States and is also associated with increased risks of non-Hodgkin lymphoma, pancreatic, bile duct, and head and neck cancers. Although the Hepatitis B vaccine is highly effective at preventing chronic infection and subsequent cancer development, vaccination rates remain low: In 2021, Hepatitis B vaccination coverage was 34.2% among adults 19 and older. This study evaluates Hepatitis B vaccination series completion among adolescents and young adults across clinic settings, demographics, and social determinants of health (SDOH) to identify gaps in vaccine coverage and reduce the incidence of Hepatitis B infection and related cancers. Methods We performed a retrospective, cross-sectional analysis using electronic health record data from adolescent medicine, pediatric infectious diseases, internal medicine-pediatrics, and family medicine clinics within the University of South Florida health system, and Ybor Youth Clinic, a community sexual health clinic within the USF pediatrics department. The sample included 456 patients aged 16-24 who were seen between January and March 2025 and had documented immunization histories. Completion of the Hepatitis B vaccination series was analyzed by clinic type and demographic and SDOH variables, including age, gender, race, ethnicity, insurance status, primary language, primary care provider, HPV and tetanus vaccination status, and comorbid conditions. Results Across 20 clinics, 422 patients (92.5%) completed the Hepatitis B vaccination series. Completion rates varied significantly across clinic types (p=0.012). Demographic factors such as gender, race, and ethnicity were not significantly associated with vaccination status (p=0.092, p=0.787, p=0.956). However, younger patients were more likely to have completed the vaccine series (p<0.001). Uninsured patients demonstrated lower completion rates compared to those with public or private insurance (p=0.045). Completion of other routine vaccines (HPV series, tetanus, and tetanus booster) was strongly correlated with Hepatitis B vaccination completion (all p<0.001). Having a primary care provider was not significantly linked to completion (p=0.271), and comorbidities such as HIV infection showed no significant association (p=0.092, p=0.124). Conclusion Hepatitis B vaccination rates in this cohort were substantially higher than national averages. However, disparities persisted based on various SDOH factors. Structural and access-related factors, particularly clinic type and insurance coverage, were more predictive of vaccine completion than demographic characteristics, suggesting structural factors have a greater influence than patient attributes in determining vaccination status. These findings highlight the need for system-level interventions to support series completion, particularly among underserved populations, to support Hepatitis B prevention and mitigate cancer-related disparities.